Feeding preferences and foraging in Larvae of Manduca sexta and Spodoptera littoralis : a laboratory study based on olfaction - Nyström, Elin (SLU/Dept. of Biosystems and Technology (from 130101), 2013)

(untitled)
Larvae of Lepidopteran Manduca sexta and Spodoptera littoralis are pests of economical importance in several horticultural and agricultural crops. Knowledge of insect feeding preferences and behavior is crucial in order to find economically and ecologically sustainable solutions to the problems caused by these herbivores.